CARDIOLOGICAL MANAGEMENT OF PREGNANT WOMEN IN THE UDMURT REPUBLIC - I. R. Gaisin; R. M. Valeeva; L. V. Shilina; N. Yu. Chernisheva; N. I. Maksimov (Столичная издательская компания, 2016)
Aim. To assess the efficacy of specialized management of pregnant women with cardiovascular diseases (CVD) in the Udmurt Republic (UR) of Russia. Material and methods. In prospective and retrospective study we investigated pregnancy outcomes in all 17948 women in management system created for pregnant patients with CVD in the UR from 2000 to 2007. The system comprises specialized outpatient and inpatient departments and an obstetric hospital within the regional cardiological centre. Pregnant women had different CVD including hypertension, congenital and rheumatic heart disease, cardiac arrhythmias, noncoronary myocardial disease, disorders and autoimmune diseases of connective tissue, etc. Results. Perinatal mortality decreased by 41,1% from 11,2‰ in 2000 to 6,6‰ in 2007. During 8 years, no one woman died. Conclusion. The management system for pregnant women with CVD within the regional cardiological clinic makes it possible to reduce of maternal and perinatal mortality rates significantly.